2008
DOI: 10.1007/s10661-008-0286-6
|View full text |Cite
|
Sign up to set email alerts
|

Local and landscape scale factors influencing edge effects on woodland salamanders

Abstract: We examined local and landscape-scale variable influence on the depth and magnitude of edge effects on woodland salamanders in mature mixed mesophytic and northern hardwood forest adjacent to natural gas well sites maintained as wildlife openings. We surveyed woodland salamander occurrence from June-August 2006 at 33 gas well sites in the Monongahela National Forest, West Virginia. We used an information-theoretic approach to test nine a priori models explaining landscape-scale effects on woodland salamander c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Within these sites, coverboards were ≥30 m from habitat edges. Research in West Virginia examining woodland salamander responses to edge effects with edge types similar to those in our study area (i.e., woodlands adjacent to permanent grassy openings) indicated that woodland salamander responses were largely confined to within 20 m of opening edges [16]. Coverboards consisted of three white oak boards, with two boards on the bottom and one board placed on top for a total dimension of 30 cm × 46 cm × 5 cm.…”
Section: Salamander Samplingmentioning
confidence: 86%
See 1 more Smart Citation
“…Within these sites, coverboards were ≥30 m from habitat edges. Research in West Virginia examining woodland salamander responses to edge effects with edge types similar to those in our study area (i.e., woodlands adjacent to permanent grassy openings) indicated that woodland salamander responses were largely confined to within 20 m of opening edges [16]. Coverboards consisted of three white oak boards, with two boards on the bottom and one board placed on top for a total dimension of 30 cm × 46 cm × 5 cm.…”
Section: Salamander Samplingmentioning
confidence: 86%
“…Interestingly, Knapp et al [13] reported that the size-corrected mass (mass/SVL) of gravid P. cinereus was actually higher on recently harvested sites than within mature forests in the southern Appalachian Mountains of Virginia and West Virginia, suggesting that forest canopy removal did not adversely impact physical condition. The apparent lack of differences in physical condition of salamanders inhabiting forest and open habitats may indicate that Plethodon cinereus is more tolerant of habitat alterations than previously suspected [10,11,37,38]. Woodland salamander habitat suitability is strongly influenced by surface moisture levels [3,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved oxygen levels also can be reduced by sediment loading [32,[35][36][37][38]. Ultimately, high fine sediment loads can alter community composition and disrupt trophic level interactions [21,24,27,33,[39][40][41][42][43]. Much of this information was developed from studies of sediment derived from land uses other than forestry or from sites without BMPs.…”
Section: Sedimentmentioning
confidence: 99%
“…Several forest amphibians occur at lower abundances in forest within 25–35 m of clearcut edges, and juvenile forest amphibians have trouble dispersing across open habitats . At five conventional gas well sites in West Virginia, three salamander species were more abundant closer to the forest edge, but less so in the drier southwestern aspect than in the moister northeastern aspect; edge effect was offset by rock and coarse woody debris (CWD) microhabitats . Organisms sensitive to forest fragmentation include lichens and bryophytes, orchids, other herbs, the West Virginia white butterfly ( Pieris virginiensis ), amphibians, and birds .…”
Section: Assessing Biodiversity Riskmentioning
confidence: 99%
“…48,49 At five conventional gas well sites in West Virginia, three salamander species were more abundant closer to the forest edge, but less so in the drier southwestern aspect than in the moister northeastern aspect; edge effect was offset by rock and coarse woody debris (CWD) microhabitats. 50 Organisms sensitive to forest fragmentation include lichens and bryophytes, 51 orchids, 52 other herbs, 53 the West Virginia white butterfly (Pieris virginiensis), 54 amphibians, 8,48,55 and birds. [56][57][58][59] Orchids are among the taxa most sensitive to habitat change in that many orchid species occur in small, isolated populations and depend on narrow ranges of soil moisture, organic matter, light, and nutrients; they also have complex obligate relationships with mycorrhizal fungi and pollinators.…”
Section: Hydraulic Fracturingmentioning
confidence: 99%